Magnetic-field manipulation of circularly polarized photoluminescence in chiral perovskites. Issue 2 (8th December 2021) - Pan, Ruiheng; Wang, Kai; Yu, Zhi-Gang
Abstract : A joint experimental and theoretical study is performed for the magnetic field manipulation of circularly polarized photoluminescence in chiral perovskites, in order to reveal the chirality-induced spin–orbit coupling. Abstract : The introduction of chiral organic ligands into hybrid organic–inorganic perovskites (HOIPs) results in chiral perovskites, which exhibit natural optical activities (NOAs) such as circularly polarized luminescence (CPL). CPL can be observed in achiral HOIPs under a magnetic field as well. Here, we systematically study the temperature- and magnetic field-dependence of both circular polarization and total intensity in chiral HOIPs. Pronounced CPL polarization is observed in polycrystalline films of chiral HOIPs, which can be further tuned by an applied magnetic field. The magnetic field also modifies the total intensity of CPL, giving rise to magneto-PL in chiral HOIPs, which is observable even at room temperature. The observed field and temperature-dependence of polarization can be well accounted for by a recently developed theory of chiral HOIPs, where the materials' helicity gives rise to a novel spin–orbit coupling (SOC). The observed MPL can be quantitatively accounted for by the interplay of exciton fine structures and the magnetic field. Our study suggests that the magnetic field provides an effective means to manipulate both the polarization and intensity of CPL in chiral HOIPs, which can be exploited for novel device applications.